ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI DAN PENDAPATAN PETANI PADI ORGANIK DI SUBAK PULAGAN, KABUPATEN GIANYAR - Dwi Saraswati, I Ketut Sutrisna, Anak Agung Istri (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
The emergence of organic farming methods is a policy undertaken by the government to improve the welfare of farmers through increasing production and income and improving the quality of agricultural ecosystems in a sustainable manner. In order to achieve national and regional food security, Bank Indonesia, Bali Province, in collaboration with the Government and the Gianyar Regency Agriculture Office, formed a rice cluster demonstration plot using organic farming methods in Subak Pulagan, Tampaksiring District. The purpose of this study is to analyze the factors that affect the production and income of organic rice farmers in Subak Pulagan. The analysis technique used is path analysis. The number of samples in this study were 47 farmers. The results of this study indicate that working capital, land area, and labor have a positive and significant direct effect on production. Working capital, land area, labor and production have a positive and significant direct effect on income in Subak Pulagan. Working capital, land area, and labor have an indirect effect on income through production, so that production is an intervening variable. Keywords: income, production, working capital, land area, labor, organic rice farming.